Castration Punishment for Sex Offenders: Reproductive Health Science Review - Anak Agung Istri Dalem Cinthya Riris; Rima Wirenviona; Abadiyah Zakiah Kustantina (Jurnal Kebidanan, 2023)
Sexual crime is a form of crime in a society whose development is increasing based on their motives, traits, form, intensity, and modes. Women and children are subjected to victims of sexual crimes. The increase in sexual crimes caused the government to regulate castration punishment for sex offenders. Castration in health is surgery on the reproductive organs or using certain chemicals to reduce and eliminate sexual drive in men. The implementation of chemical castration in Indonesia is expected to have a deterrent effect on the perpetrators and prevent new cases of sexual violence. On the other hand, the implementation of chemical castration is thought to be against human rights. Related to the reproductive health perspective, castration as punishment can cause a decreasing reproductive function to come into sexual desire. Behavior aberration is a form of integrated multifactorial motives and the reason will not always biological factor or sexual drive. This article discusses the handling of sexual crimes that are comprehensively studied, especially in the area of reproductive health.